Estimates of genetic parameters for iron, zinc, magnesium and phosphorus in common bean grains - Buratto, Juliana Sawada; Moda-Cirino, Vania (Comunicata Scientiae, 2017)
Information about genetic parameters is required for the development of cultivars with higher nutritional value. In this sense, this study aimed to estimate the following genetic parameters: genetic variances, heritability coefficients in narrow and broad sense and predict the selection gain for the Fe, Zn, Mg and P contents in common bean grains. The crosses were made between cultivars: FT Nobre x IPR Gralha and Diamante Negro x IPR Chopim. The genitors (P1 and P2) were crossed resulting in F1 and F2 generations and backcrosses BC1 (P1 x F1) and BC2 (P2 x RC2). The mineral contents of Fe, Zn, Mg and P in grains were measured by nitric-perchloric digestion using atomic emission spectrometry coupled with plasma (ICP-OES). The predicted gains for the first cycle of selection were positive, indicating the viability of the increaseof the minerals Fe, Zn, Mg and P levels on common bean grains using classical breeding methods. The prediction gains obtained in the first cycle of selection resulted in values ranging from 3.24% to 15.48% for Mg and Fe, respectively. Heritability estimates in narrow sense ranged from 29.48% to 62.04% and the broad range sense heritability ranged from 45.14% to 76.36%.